Determination of ellagic acid in the wastes of walnut, chestnut, and pomegranate grown in Turkey - (:unkn) unknown (American Chemical Society, 2018)
Ellagic acid (EA) is a polyphenol, which exists in fruits and nuts in free form or derivatives, like hydrolyzable ellagitannins (ETs). EA has a chemoprotective effect in cellular models by reducing oxidative stress, and also antiproliferative and antioxidant properties in many in vitro and animal models. EA was identified and quantified by the currently developed RP-HPLC-DAD methods in the methanolic extracts of the walnut tree barks, shoots, wood sawdust, chestnut bark; three brands pomegranate (pom) juices labeled as 100% from Turkish market, lab-made pom juices from three registered varieties; and peels and pericarps of two registered pom varieties. No EA detected in the walnut samples, except for the wood sawdust extract with the amount of 39.3±8.8 mg/100g. The peak area of EA in the chestnut bark was 4.07 times more after exposure to hydrolysis reaction compared to the peak area of the EA derivative. Hydrolysis conditions optimized concerning temperature, time, and concentration of trifluoroacetic acid. The amount of EA found was 30.74 mg/100 g with the recovery of 89.20±1.98% in the chestnut bark; 80.87±1.70 mg/L, 522.64±1.81 mg/L, and 356.87±2.58 mg/L in Brand E, M, and D commercial pom juices, respectively. Home-made pom juices contained lower amounts of EA than the commercial ones with the quantities of 39.35±0.48 mg/L (Hicaz pom), 3.81±0.13 mg/L (Delibekirli pom), 10.17±0.29 mg/L (Caner pom). The EA was found to be 161.5 mg/100g and 45.00 mg/100g in Hicaz and Delibekirli pom peels; 86.5 mg/100g and 27.5 mg/100g in Hicaz and Delibekirli pom pericarps. The recovery of lab-made and commercial juices found at 98.36±1.14% and 96.81±2.55%, respectively. © 2018 American Chemical Society.